2012
DOI: 10.1227/neu.0b013e318235ade1.
|View full text |Cite
|
Sign up to set email alerts
|

Surgical vs Nonoperative Treatment of Hadley Type IIA Odontoid Fractures

Abstract: Hadley type IIA odontoid fractures are inherently unstable and impede proper realignment. These fractures have a significantly increased risk for secondary loss of reduction and bony nonunion, particularly after nonoperative management. Early surgery should be considered to avoid further complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
0
11
1
Order By: Relevance
“…Our bony healing rate is reportedly lower than that reported in other series 2,4,5,10,13,16,19,20,22,23,25,26,32 ( Table 6). This may be related to a number of factors.…”
Section: Discussioncontrasting
confidence: 69%
“…Our bony healing rate is reportedly lower than that reported in other series 2,4,5,10,13,16,19,20,22,23,25,26,32 ( Table 6). This may be related to a number of factors.…”
Section: Discussioncontrasting
confidence: 69%
“…The fusion rate of 95% after OS fixation in our series was comparable with the results in the available literature (87-100%). [6,13,14,18,[33][34][35] Many authors have recommended PF as the procedure of choice for the surgical approach in type IIA and type III fractures due to a slightly higher non-union rate associated with OS fixation. Our results of 95.8% and 100% fusion rates in type II and high type III fractures are comparable with the published literature.…”
Section: Discussionmentioning
confidence: 99%
“…Shrinivasan et al [40] could successfully place OS in 84.6% type II fractures with an 82% fusion rate. Aldrian et al (2011) [35] showed a good fusion rate of 87% after OS fixation in type IIA fracture and have also recommended it as the first line of management in comminuted odontoid fractures. Other authors, in a contrasting opinion, have recommended against utilizing an OS fixation in type IIA comminuted fractures due to the high non-union rates and have preferred the PF techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,7,12 Numerous studies have described the morbidity associated with this type of treatment, increasing to 66% for major complications. 25,44 Other studies have reported treatment with a rigid collar or a soft collar but for Type I or III fractures.…”
Section: Discussionmentioning
confidence: 99%